3-Indolepropionic acid upturned male reproductive function by reducing oxido-inflammatory responses and apoptosis along the hypothalamic-pituitary-gonadal axis of adult rats exposed to chlorpyrifos. (November 2021) - Owumi, Solomon E.; Otunla, Moses T.; Arunsi, Uche O.; Najophe, Eseroghene S.
Abstract: We examined the effect of 3-Indolepropionic acid (3-IPA), an antioxidant on the organophosphorus pesticide chlorpyrifos (CPF)-induced reproductive toxicity in rats. The five experimental rat cohorts were treated per os for 14 consecutive days as follows: Control (Corn oil 2 mL/kg body weight), CPF alone (5 mg/kg), 3-IPA alone (40 mg/kg) and the co-treated rat cohorts (CPF:5 mg/kg + 3-IPA: 20 or 40 mg/kg). Biomarkers of testicular and epididymal function, oxidative stress, myeloperoxidase (MPO) activity and the levels of nitric oxide (NO), reactive oxygen and nitrogen (RONS) species and lipid peroxidation (LPO) were assessed. Also, tumour necrosis factor-alpha (TNF-α), Bcl-2-associated X (Bax) and B cell lymphoma 2 (Bcl-2) proteins were estimated, and tissue histology was microscopically examined. CPF alone significantly ( p < 0.05 ) increased biomarkers of reproductive toxicities were averted in rats co-treated 3-IPA. Decreases in antioxidants and increases in lipid peroxidation and reactive oxygen and nitrogen species were lessened ( p < 0.05 ) in CPF and 3-IPA co-treated rats. CPF mediated increases in TNF-α, NO, Bax, and MPO activity was reduced ( p < 0.05 ) in the epididymis, testes, and hypothalamus of rats co-treated with 3-IPA. In addition, Bcl-2 expression was increased in rats co-treated with 3-IPA dose-dependently. Histopathological examination revealed severe lesions induced by CPF were prevented in rats co-treated with 3-IPA. Our findings demonstrate that exogenous 3-IPA reduced CPF-induced oxidative stress, inflammation, and apoptosis in the epididymis and testes of male rats.